Unraveling the Reshaping of Human Resource Management Function: the mediating role of artificial intelligence - Samuel Bangura; Anos Chitamba Chitamba; Lucia Zithobile Ngidi; Sizwe Mbona (International Journal of Management and Data Analytics)
The dynamic nature of the modern work environment is characterized by increasing complexity, diversity, and adaptability beyond traditional workplaces. This shift is predominantly driven by advanced technologies that are transforming human resource management functions within organizations. The integration of artificial intelligence AI into HR practices represents a significant development, enhancing organizational capabilities while streamlining manual processes. This study aims to analyse the transformative impact of AI on HR management, evaluate its influence on HR practices, and identify the associated challenges and opportunities associated the adoption of AI in HRM. A quantitative research methodology was employed, utilizing a survey instrument based on a 5.0 Likert scale. The sample consisted of 103 employees from various departments and levels within a selected organization in Durban, out of a targeted population of 500 employees, selected through simple random sampling. The results indicate that AI supports HRM professionals in executing tasks more efficiently and facilitates data analysis and process optimization. Additionally, the findings suggest that AI contributes to streamlining HR processes and has a positive impact on work-life balance, demonstrating that automation can improve both operational efficiency and employee well-being. However, the study also identifies potential challenges associated with AI adoption, including concerns related to algorithmic bias, data privacy, transparency, and employee apprehensions. Despite these obstacles, AI has the potential to significantly enhance HRM practices and support effective talent management strategies. It is recommended that organizations focus on increasing AI literacy among employees and involve staff in the development of AI policies to promote acceptance and reduce resistance to technological advancements.